Double-cross hybrid selection for aluminum tolerance - Magnavaca, Ricardo; Gama, Elto Eugenio Gomes e; Filho, Antônio F.C. Bahia; Fernandes, Fernando T. (Pesquisa Agropecuaria Brasileira, 2014)
A set of maize inbred lines selected based on evaluation per se and as top-cross hybrids for aluminum tolerance, were used for obtaining Al tolerant double-cross experimental hybrids. These double-cross hybrids originated from the crossing of ten different single-cross hybrids with two common Al tolerant single-cross testers, HS1 and HS2, obtaining two sets of ten double-cross hybrids. Yield and stability of the Al tolerant hybrids were evaluated in high fertile soils and compared to less Al tolerant commercial hybrids. Aluminum tolerance was assessed in a nutrient solution with 222 µmol Al L-1 and 45 µmol P L-1. Yield and yield stability were tested in field trials at five sites on soils where maize is normally grown as well as cerrado soils. These results indicate the possibility of obtaining superior Al tolerant specific crosses from selected Al tolerant inbred lines. The nutrient solution technique described was effective in detecting superior Al tolerant crosses. It was not possible to find a negative correlation between yield and high Al tolerance, and high Al tolerance may be added to high yield and stable genotypes.